An investigation on worn surfaces of chopped glass fibre reinforced polyester through SEM observations - ELTAYEB, N; YOUSIF, B; YAP, T (ELSEVIER SCI LTD, 2008)
The wear mechanisms of chopped strand mat (CSM) glass fibre reinforced polyester (CGRP) composite subjected to dry sliding against smooth stainless steel counterface (R-a=0.06 mu m) were studied using a pin-on-disc technique. The effects of normal load (30 - 90 N), sliding velocity (2.8 - 3.9 m/s) and sliding distance (0.7 - 3.5 km) on friction and wear behaviour of the CGRP composite in two different CSM orientations (parallel and anti-parallel) were measured. The worn surfaces of the CGRP composite specimens for each specific test condition were examined using scanning electron microscopy (SEM).